Peningkatan Kapasitas Masyarakat Kawasan Wisata Goa Pawon - vyana lohjiwa; Riadi Darwis; Endah Trihayuningtyas; Tatang Sophian; Renalmon Hutahaean (Politeknik Pariwisata NHI Bandung, 2021)
Goa Pawon is one of tourist destination that has begun to be known by West Java’s people. In Goa Pawon, there are local people which becomes “ojeg”/motorcycle taxi drivers who often take tourists to Goa Pawon, but the survey results shown that they have not optimized their capacity to be able to act as a frontliner services for tourism. In fact, if they have basic knowledge of tourism and how to serve tourists excellently, tourists will feel satisfied whose impact is to increase their income as well as become agents that can accelerate the promotion and popularity of Goa Pawon.